In vivo Host Environment Alters Pseudomonas aeruginosa Susceptibility to Aminoglycoside Antibiotics - Pan, Xiaolei; Dong, Yuanyuan; Fan, Zheng; Liu, Chang; Xia, Bin; Shi, Jing; Bai, Fang; Jin, Yongxin; Cheng, Zhihui; Jin, Shouguang; Wu, Weihui (Frontiers in Cellular and Infection Microbiology, 2017)
During host infection, Pseudomonas aeruginosa coordinately regulates the expression of numerous genes to adapt to the host environment while counteracting host clearance mechanisms. As infected patients take antibiotics, the invading bacteria encounter antibiotics in the host milieu. P. aeruginosa is highly resistant to antibiotics due to multiple chromosomally encoded resistant determinants. And numerous in vitro studies have demonstrated the regulatory mechanisms of antibiotic resistance related genes in response to antibiotics. However, it is not well known how host environment affects bacterial response to antibiotics. In this study, we found that P. aeruginosa cells directly isolated from mice lungs displayed higher susceptibility to tobramycin than in vitro cultured bacteria. In vitro experiments demonstrated that incubation with A549 and differentiated HL60 (dHL60) cells sensitized P. aeruginosa to tobramycin. Further studies revealed that reactive oxygen species produced by the host cells contributed to the increased bacterial susceptibility. At the same concentration of tobramycin, presence of A549 and dHL60 cells resulted in higher expression of heat shock proteins, which are known inducible by tobramycin. Further analyses revealed decreased membrane potential upon incubation with the host cells and modification of lipopolysaccharide, which contributed to the increased susceptibility to tobramycin. Therefore, our results demonstrate that contact with host cells increased bacterial susceptibility to tobramycin.